CYCLIC NUCLEOTIDE-GATED ION CHANNELs 14 and 16 Promote Tolerance to Heat and Chilling in Rice . Issue 4 (11th June 2020) - Cui, Yongmei; Lu, Shan; Li, Zhan; Cheng, Jiawen; Hu, Peng; Zhu, Tianquan; Wang, Xiang; Jin, Mei; Wang, Xinxue; Li, Luqi; Huang, Shuying; Zou, Baohong; et al.
Abstract : Cyclic nucleotide-gated ion channels in rice promote tolerance to both heat and chilling and affect the calcium response to temperature stresses. Abstract: Calcium signaling has been postulated to be critical for both heat and chilling tolerance in plants, but its molecular mechanisms are not fully understood. Here, we investigated the function of two closely related cyclic nucleotide-gated ion channel (CNGC) proteins, OsCNGC14 and OsCNGC16, in temperature-stress tolerance in rice ( Oryza sativa ) by examining their loss-of-function mutants generated by genome editing. Under both heat and chilling stress, both the cngc14 and cngc16 mutants displayed reduced survival rates, higher accumulation levels of hydrogen peroxide, and increased cell death. In the cngc16 mutant, the extent to which some genes were induced and repressed in response to heat stress was altered and some Heat Shock factor ( HSF ) and Heat Shock Protein ( HSP ) genes were slightly more induced compared to the wild type. Furthermore, the loss of either OsCNGC14 or OsCNGC16 reduced or abolished cytosolic calcium signals induced by either heat or chilling stress. Therefore, OsCNGC14 and OsCNGC16 are required for heat and chilling tolerance and are modulators of calcium signals in response to temperature stress. In addition, loss of their homologs AtCNGC2 and AtCNGC4 in Arabidopsis ( Arabidopsis thaliana ) also led to compromised tolerance of low temperature. Thus, this study indicates a critical role of CNGC genes in both chilling and heat tolerance in plants, suggesting a potential overlap in calcium signaling in response to high- and low-temperature stress.